Density, Morphology and Egg Clusters of Pila scutata Snails at Rice Fields Area in Peringsari Village, Bali - Suartini, Ni Made; Sudatri, Ni Wayan (KnE Life Sciences, 2022)
Pila scutata is a species belonging to the Ampullariidae family. One of the habitats of the snail is rice fields. Snails are used as an alternative protein source in Bali. The focus of this research was to determine the snail density, morphology, morphometry, and egg clusters in rice fields in the Selat District of the Karangasem Regency in Bali. Snails were collected in the morning by erecting a 1m x 1m quadrat in each corner of the rice field. Snails ranging in size from small to large were collected in the quadrats, on the surface of the water, in the water, and attached to aquatic plants. Snail egg clusters were discovered while exploring the rice fields where snail samples were collected. Sampling was repeated three times. Snail and egg cluster samples were brought to the lab for examination. The density, frequency of presence, distribution pattern, morphology, and morphometry of the snails were all calculated. The number of eggs in one egg cluster was determined by separating each egg from the egg cluster. According to the findings, the snail density was 3.75 individuals/m2, the presence frequency was absolute, and the distribution pattern was regular. The shell height was 17.02-31.09 mm, and the snails had a subglobose shape with brown transverse band. A single egg cluster could contain 29-67 eggs. Keywords: mollusk, ampullariidae, apple snails, Pila